Techno-economic optimisation of carbon dioxide purification and allocation for industrial sinks: a two-stage simulation and optimisation framework - Razan Sawaly (19170910) (2025)
Carbon capture, utilisation, and storage (CCUS) is recognised as an important pathway for reducing greenhouse gas emissions in hydrocarbon-producing regions such as Qatar. However, the high energy and cost requirements of CO2 capture and purification remain a barrier to large-scale deployment. This study hypothesises that integrating process simulation with optimisation can reduce costs by aligning purification levels with the specific requirements of multiple industrial sinks. A two-stage amine absorption system was simulated in Aspen HYSYS to generate CO2 streams of different purities, and a regression-based cost model from 45 scenarios was embedded into a nonlinear optimisation framework implemented in GAMS. The optimisation identified an economically optimal strategy with a splitting ratio of 6.61 % and a recovery rate of 74.2 %, achieving a minimum system cost of 4.26 million USD/year. CO2 purification costs ranged from 73.89 USD/ton at 91.2 % purity to 155.60 USD/ton at 99.9 % purity, demonstrating a nonlinear cost escalation with increasing purity. The results show that directing moderate-purity CO2 to GTL and methanol, and reserving ultra-pure CO2 for urea and EOR, enhances overall profitability. This scalable framework provides a practical tool for strategic CCUS planning in Qatar and similar industrial contexts, linking technical performance with economic decision-making. Other Information Published in: Energy Conversion and Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.encoman.2025.120559